2018
DOI: 10.1002/eco.2045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a large flood on woody vegetation along the regulated Missouri River, USA

Abstract: In 2011, a large, long‐duration flood occurred on the regulated Missouri River following six decades without flooding. This study evaluated the effects of the flood on riparian forest structure and composition. In 2012, 168 forest sites sampled in 2006–2009 were resampled on five floodplain segments between Montana and Missouri, with 80 sampled again in 2013–2014. Changes in riparian forest area over 2006–2012, by age class and segment, were assessed using aerial imagery and GIS. Repeated‐measures analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
(131 reference statements)
2
8
0
Order By: Relevance
“…Greene and Knox (2014) observed redcedar mortality on flooded lower surfaces, whereas there were healthy redcedar individuals on non‐flooded upper surfaces. Boever et al (2019) reported a mixture of dead and live individual redcedars on many riverine forest sites after the flood within the study area. Aside from the visual observations by Greene and Knox (2014) and the stand‐based estimates of redcedar declines by Dixon et al (2015) and Boever et al (2019), there has been no comprehensive assessment of the effects of the 2011 flood on redcedar within the Missouri River floodplain.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Greene and Knox (2014) observed redcedar mortality on flooded lower surfaces, whereas there were healthy redcedar individuals on non‐flooded upper surfaces. Boever et al (2019) reported a mixture of dead and live individual redcedars on many riverine forest sites after the flood within the study area. Aside from the visual observations by Greene and Knox (2014) and the stand‐based estimates of redcedar declines by Dixon et al (2015) and Boever et al (2019), there has been no comprehensive assessment of the effects of the 2011 flood on redcedar within the Missouri River floodplain.…”
Section: Introductionmentioning
confidence: 88%
“…This flood was different from pre‐regulation floods because of its exceptionally long duration, as some locations were inundated for more than 3 months (e.g., June to September) (Dixon et al, 2015) (Figure 2 inset). As a result, the flood killed a significant proportion of redcedar and Russian‐olives within the floodplain (Boever, Dixon, Johnson, Scott, & Malloy, 2019; Dixon et al, 2015; Greene & Knox, 2014). Greene and Knox (2014) observed redcedar mortality on flooded lower surfaces, whereas there were healthy redcedar individuals on non‐flooded upper surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…One is that factors cannot be explained by climate variables are classified into human factors by RESTREND. Therefore, fires, floods, pests and diseases that cause vegetation dynamic could be mistaken for human activities (Liu et al 2013;Boever et al 2019;Yuan et al 2017). Another is RESTREND cannot detect human activities which driving vegetation throughout the study period.…”
Section: Effects Of Human Activities and Limitations Of Restrendmentioning
confidence: 99%
“…Asterisks indicate significant differences before and after the flood, for a given type of plot, following a mixed model (p < .05). Sediments were not analyzed in any of the reset plots changes to plant composition in unregulated (e.g., Renöfält et al, 2007;Stromberg et al, 1993) and regulated rivers (Boever, Dixon, Johnson, Scott, & Malloy, 2019;Dixon et al, 2015).…”
Section: Figurementioning
confidence: 99%